1996
DOI: 10.1002/(sici)1097-4652(199609)168:3<625::aid-jcp15>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of heparan sulfate proteoglycan by stimulated endothelial cells: Evidence for proteolysis of cell-surface molecules

Abstract: Activation of endothelial cells by cytokines and endotoxin causes procoagulant and pro-inflammatory changes over a period of hours. We postulated that the same functional state might be achieved more rapidly by changes in the metabolism of heparan sulfate, which supports many of the normal functions of endothelial cells. We previously found that binding of anti-endothelial cell antibodies and activation of complement on endothelial cells causes the rapid shedding of endothelial cell heparan sulfate. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(29 citation statements)
references
References 59 publications
1
27
0
1
Order By: Relevance
“…It is well known that the interaction of MAC with EC can result in a number of pro‐inflammatory actions and it triggers changes similar to those induced by cytokines. MAC induces, within minutes, the formation of intracellular gaps, 27 the expression of P‐selectin 28 and the activation of proteinases that cleave and release heparan sulphate proteoglycan from EC surfaces 29 . In addition, MAC stimulates, over a period of hours, the up‐regulation of tissue factor, cyclooxygenase‐2 and chemokines 22,30–32 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the interaction of MAC with EC can result in a number of pro‐inflammatory actions and it triggers changes similar to those induced by cytokines. MAC induces, within minutes, the formation of intracellular gaps, 27 the expression of P‐selectin 28 and the activation of proteinases that cleave and release heparan sulphate proteoglycan from EC surfaces 29 . In addition, MAC stimulates, over a period of hours, the up‐regulation of tissue factor, cyclooxygenase‐2 and chemokines 22,30–32 .…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-1 has been shown to be shed after treatment by thrombin and epidermal growth factors, and its shedding can be mediated by G protein-coupled receptors (GPCRs), protein tyrosine kinase receptors, and a tissue inhibitor of the metalloproteinase-3-sensitive pathway (9,34). HS is shed after the treatment of cultured ECs with complement (13) and endotoxin (5). Prior studies suggested that stimulation of the GPCRs with N-formylmethionyl-leucyl-phenylalanine (fMLP) results in enhanced WBC adhesion in postcapillary venules in mesentery (rat) because of shedding of HS proteoglycans that in turn exposes greater amounts of ICAM-1 to facilitate adhesion of the CD11a,b/CD18 receptor on the leukocyte (20).…”
mentioning
confidence: 99%
“…Due to the heterogeneity of its composition and its location, the glycocalyx plays a critical role as a protective barrier in maintaining vessel wall permeability and modulating blood cell-vessel wall interactions 25 . The transplant process activates and injures graft endothelium, causing shedding of the glycocalyx and loss of regulators, creating a pro-inflammatory, pro-coagulant environment 6 . While the graft eventually recovers, this early insult can contribute to primary non-function and cause long-term detrimental effects.…”
Section: Introductionmentioning
confidence: 99%